EFEKTIVITAS SENYAWA EKSTRAK BAHAN ALAMI SEBAGAI PENGAWET DAN PENURUN KOLESTEROL DAGING RUMINAN - Nitema Gulo; Puteri Aisyah; Pahriadi Pahriadi; Fajriah Novia Susanti; Siti Rahma Dewi; Habibah Habibah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
Meat is one source of protein that is widely consumed by humans. In general, the meat is largely derived from ruminant livestock such as cattle and buffalo. In consuming this meat almost all people still have difficulty in processing because of low shelf life and high cholesterol content so it can have a negative impact on health. To maintain the shelf life of meat can be preserved by using chemicals such as citric acid. However, the use of chemicals for preservation will affect the quality of meat that will have a negative impact on health. So to overcome this in this study was conducted with the aim to examine the natural materials that exist in nature to serve as materials that have more use in processing the production of livestock, especially meat. These natural ingredients in addition to preserving also lower cholesterol levels of meat. The method used in this research is to blend the three organic materials that have been provided with the ratio of nutmeg, belimbing wuluh and garlic respectively 10%. Then mixed with ruminant meat (beef, goat, buffalo), soaked with each 0, 10, 20, 30 and 40 minutes sampling for bacteria testing, cholesterol test, pH test, water binding test and cooking shrinkage test.